Predicting family caregiver psychosocial functioning in palliative care - Hudson, P.; Hayman-White, K.; Aranda, S.; Kristjanson, Linda (Centre for Bioethics, Clinical Research Institute of Montreal, 2006)
Health professionals are expected to support family caregivers of patients requiring palliative care. However, there is a dearth of empirical evidence to help clinicians identify caregivers who might be at risk of poor psychosocial functioning.This secondary analysis of baseline data from a larger study sought to determine if it was possible to predict the pyschosocial functioning of family caregivers who were supporting a relative with advanced incurable cancer.Data from 35 primary family caregivers obtained at the start of home-based palliative care services and five weeks later was used in the analysis. Instruments to measure careigver preparedness, competence, mastery, social support, anxiety, and self-efficacy were used.Cluster and logistic analyses revealed that self-reported 'anxiety' and competence' subscale total scores at time of commencement of home-based palliative care services were associated with caregivers at risk of lower levels of psychosocial functioning five weeks later.This study suggests that it may be possible to identify family caregivers who are at risk for poorer psychosocial functioning. However, replication in a larger sample is required before this screening approach can be recommended for clinical use.